Copper-catalyzed multi-component reactions synthesis of nitrogen-containing polycyclic compounds - Ohta, Yusuke (Springer theses., 2011)
A copper-catalyzed direct synthesis of 2-(aminomethyl)indoles by catalytic domino reaction including multi-component coupling was developed, and is the first example of a three-component indole formation without producing salts as a byproduct. Based on this reaction, a copper-catalyzed synthesis of 3-(aminomethyl)isoquinoline was accomplished which represents an unprecedented isoquinoline synthesis through a four-component coupling reaction. Following these results, extensive application studies using one-pot palladium-, acid-, or base-promoted cyclization revealed that indole- or isoquinoline-fused polycyclic compounds can be readily synthesized through multi-component reactions. As the concept of Green Chemistry becomes ever more important, these findings may provide efficient and atom-economical approaches to the diversity-oriented synthesis of bioactive compounds containing a complex structure. This could lead to development of promising drug leads with structural complexity. The work of this thesis will go on to inspire the synthetic research of many readers.